Vibration measurements of a wire scanner – Experimental setup and models. (March 2016) - Herranz, Juan; Barjau, Ana; Dehning, Bernd
Abstract: In the next years the luminosity of the LHC will be significantly increased. This will require a much higher accuracy of beam profile measurement than actually achievable by the current wire scanner. The new performance demands a wire travelling speed up to 20 m s −1 and a position measurement accuracy of the order of 1 μm. The vibrations of the mechanical parts of the system and particularly the vibrations of the thin carbon wire have been identified as the major error sources of wire position uncertainty. Therefore the understanding of the wire vibrations has been given high priority for the design and operation of the new device. This article presents a new strategy to measure the wire vibrations based on the piezoresistive effect of the wire itself. An electronic readout system based on a Wheatstone bridge is used to measure the variation of the carbon wire resistance, which is directly proportional to the wire elongation caused by the oscillations. Graphical abstract: Highlights: The thin carbon wire shows vibrations which are a source of uncertainty. New strategy measure those vibrations based on the piezoresistive effect of the wire. Strain gauges have been used for measurements verification of the fork deflections. This technology can be easily implemented in current operating devices.